Frontal Dysfunctions of Impulse Control – A Systematic Review in Borderline Personality Disorder and Attention-Deficit/Hyperactivity Disorder - Sebastian, Alexandra; Jung, Patrick; Krause-Utz, Annegret; Lieb, Klaus; Schmahl, Christian; Tüscher, Oliver (Frontiers in Human Neuroscience, 2014)
Disorders such as borderline personality disorder (BPD) or attention-deficit/hyperactivity disorder (ADHD) are characterized by impulsive behaviors. Impulsivity as used in clinical terms is very broadly defined and entails different categories including personality traits as well as different cognitive functions such as emotion regulation or interference resolution and impulse control. Impulse control as an executive function, however, is neither cognitively nor neurobehaviorally a unitary function. Recent findings from behavioral and cognitive neuroscience studies suggest related but dissociable components of impulse control along functional domains like selective attention, response selection, motivational control and behavioral inhibition. In addition, behavioral and neural dissociations are seen for proactive versus reactive inhibitory motor control. The prefrontal cortex with its sub-regions is the central structure in executing these impulse control functions. Based on these concepts of impulse control, neurobehavioral findings of studies in BPD and ADHD were reviewed and systematically compared. Overall, BPD patients exhibited prefrontal dysfunctions across impulse control components rather in orbitofrontal, dorsomedial and dorsolateral prefrontal regions, whereas ADHD patients displayed disturbed activity mainly in ventrolateral and medial prefrontal regions. Prefrontal dysfunctions, however, varied depending on the impulse control component and from disorder to disorder. This suggests a dissociation of impulse control related frontal dysfunctions in BPD and ADHD, although only few studies are hitherto available to assess frontal dysfunctions along different impulse control components in direct comparison of these disorders. Yet, these findings might serve as a hypothesis for the future systematic assessment of impulse control components to understand differences and commonalities of prefrontal cortex dysfunction in impulsive disorders.